The 21st-century skills among public health undergraduate students in autonomous universities in Thailand after the COVID-19 pandemic: 10.55131/jphd/2025/230316 - Panthumas, Suphawadee; Zaw, Kaung; Kittipichai, Wirin (Journal of Public Health and Development, 2025)
Adopting new skills is essential for success in the 21st century, especially in education and public health. As career transitions and lifelong learning increase, educational institutions are adapting their approaches. They are integrating technology and resources to help students apply knowledge effectively. This cross-sectional study employed stratified-cluster random sampling approach to assess 21st-century skills and six related factors—academic year, esteem for oneself, esteem for others, active learning, qualities of effective teachers, and learning environment—among 537 second- to fourth-year undergraduate public health students from four autonomous universities in Thailand. Data were collected using self-administered questionnaires between January and March 2023. The reliability coefficients of the scales ranged from 0.78 to 0.93. Data were analyzed using descriptive statistics, one-way ANOVA, Pearson’s product-moment correlation, and stepwise multiple linear regression, with the significance level set at less than 0.05. Research findings indicated that 60.5% of students had high levels of 21st-century skills, while 39.5% had moderate levels. Fourth-year students scored higher on these skills compared to those in the second and third years. Five factors, including two subscales of self-esteem and three dimensions of teaching and learning management during the COVID-19 pandemic, were identified as predictors of 21st-century skills, accounting for 54.2% of the variance. To provide early-year students with the necessary skills and opportunities for lifelong learning, curriculum administrators should promote activities that enhance 21st-century skills, boost self-esteem, and provide adequate support for learners, instructors, and learning environments.